The impactful implementation of the Merdeka Curriculum administration at SD Negeri 008 Benteng through a deep learning approach - Ahmad, Ahmad; Putra, Edi Susrianto Indra; Khairuddin, Khairuddin; Muthalib, A (Mitra PGMI: Jurnal Kependidikan MI, 2025)
This study aims to describe the implementation of impactful curriculum administration based on the Merdeka Curriculum at SD Negeri 008 Benteng, Sungai Batang District, through a deep learning approach. This descriptive qualitative research involved teachers, school administrators, and education stakeholders as the main informants. Data collection was conducted through interviews, observation, and documentation analysis. The research gap identified shows that while 80% of Indonesian schools have implemented the Merdeka Curriculum since 2024, significant challenges remain in aligning administrative documentation with reflective and deep learning-oriented practices. The findings reveal that the school's curriculum administration has begun to adapt to Merdeka Curriculum principles, emphasizing student-centeredness, flexibility, and meaningful learning experiences. However, critical gaps exist in integrating the three pillars of deep learning (mindful, meaningful, durable) into administrative processes. The study introduces a novel framework for "Reflective Administrative Documentation" that bridges traditional bureaucratic requirements with transformative educational practices. This research contributes to the field by providing empirical evidence of successful integration strategies and proposing a replicable model for other elementary schools. The study suggests that continuous professional development, leadership support, and systematic documentation reform are key to ensuring impactful curriculum implementation that truly transforms learning outcomes.